Approximate expression for the energy of a D-dimensional anharmonic oscillator - Dutra, Alvaro de Souza [UNESP]; de Castro, A. S.; da Silva, E. A.; Castilho, LCO (Iop Publishing Ltd, 2003)
An approximate expression is constructed for the energy of an anharmonic potential with centrifugal barrier. In order to obtain such an analytical expression, the quasi-exact solvability is used and then a fitting of these exact solutions is done.